Pengembangan Manajemen Diklat Berbasis Digitalisasi - Nasution, Abdul Fattah; Widyana, Tasya; Oktaviani, Dita; Masliani, Dessy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of writing the article is to describe in general the development of training management in the digital era or the 4.0 industrial revolution in improving the quality of human resources themselves, which of course can be useful for individuals and institutions. writing in the article used a qualitative approach with the Systematic Literature Review Method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Metaanalysis) model. The data search results are used in the form of data collection methods such as journals or articles obtained from national and international journals or articles contained in Scopus, Emerald, and Google Scholar. From the findings and discussion, it can be concluded that the faster the times, the fiercer the competition between institutions, therefore the greater the demands of an institution for the development of quality human resources. In practice, in the digital era or industrial revolution 4.0, human resource development can be carried out effectively and efficiently through digital education and training.